Nursing interventions in treatment of emergencies in oncology - Pavić Katarina; Vešić Marija (Association of Nurses Technicians and Midwives, 2020)
Emergencies in oncology are acute exacerbations of the patient's condition that can be fatal and are caused by a tumor process or antitumor treatment. Can affect different organs or organ systems, generally are classified as: obstructive syndromes, metabolic disorders, and hematological or immunological disorders. The nurse is an important member of the team involved in the treatment of cancer patients and their interventions can contribute to reducing the rate of mortality and successful treatment of emergencies. As she spends most of her time with the patient, the nurse must be educated to recognize the symptoms and signs of emergencies, in order to provide first aid in time and inform the doctor. Nurse interventions are aimed at performing diagnostic procedures in patients, applying appropriate therapeutic measures, monitoring patients and providing health care.